Inhaled micronised gentamicin powder: a new delivery system. Issue 12 (December 1990) - Goldman, J M; Bayston, S M; O'Connor, S; Meigh, R E
Abstract : Forty patients undergoing routine bronchoscopy were randomised to receive inhaled micronised gentamicin powder (180 mg) or nebulised gentamicin solution (160 mg) one hour before the procedure. Similar levels of gentamicin were detected in bronchoalveolar lavage fluid in the two groups (micronised powder (n = 20) 9.3 (SD 9.3) mg/l, nebulised solution (n = 20) 8.0 (7.8) mg/l). The micronised gentamicin powder preparation caused cough in half the patients but this did not stop their receiving a full dose. Dry powder gentamicin may be a convenient formulation for long term inhaled treatment if the problem of cough can be overcome.